Analisis Pengungkapan K3 Dan Kontribusi SDGS di Industri Pertambangan Tahun 2024 - Anas, Nurul Inayah Aulia; Nurhidayana, Nurhidayana; Abidin, Nur Hikmah Lestari; Resmail, Aliyah Aqila (Annusfy : Journal of Multidisciplinary Research, 2025)
This study analyzes the disclosure of Occupational Health and Safety (OHS) practices and their contribution to the Sustainable Development Goals (SDGs) in the Indonesian mining sector during 2024, focusing on PT Adaro and PT Merdeka Copper Gold Tbk. Using a document-based qualitative content analysis of sustainability reports and publicly available company information, the research evaluates three dimensions policy, program, and Outcome to assess alignment with SDG 3 (Good Health and Well-being) and SDG 8 (Decent Work and Economic Growth). Findings reveal significant variations in OHS implementation. PT Adaro demonstrates strong integration with structured programs and measurable Outcomes (score 24/27), whereas PT Merdeka Copper Gold Tbk displays limited implementation impacts and largely normative disclosures (score 15/27). These findings confirm gaps in OHS integration within sustainability reporting as noted in previous literature. This study highlights the importance of measurable performance indicators to strengthen corporate accountability and contributions to national sustainability goals.